2021
DOI: 10.3390/ani11030692
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Non-Circadian Photoperiod on Growth and Puberty Onset of Brook Trout Salvelinus fontinalis Mitchill

Abstract: The aim of the present study was to assess the effects of a prolonged photoperiod on growth rate and sexual maturation in brook trout Salvelinus fontinalis. The task of the experiment was to determine the most effective light regimen capable to minimizing the effects of puberty, including impairment of somatic growth and further general characteristics. In this regard, the studied fish were reared under three photoperiod regimens in which fish were exposed to 24 h continuous light alternating with 24 or 48 h u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…For brook trout (Salvelinus fontinalis), it could be shown that a more natural light regime seems to be more suitable. Lundova et al exposed specimen to 48 h of natural photoperiod alternating with 24 h of constant light, which resulted in increased somatic growth in both sexes (Lundova et al 2021). Another positive effect was the delayed gonadal development and the onset of puberty (Lundova et al 2021).…”
Section: Light Regime-what Should Be Consideredmentioning
confidence: 99%
See 1 more Smart Citation
“…For brook trout (Salvelinus fontinalis), it could be shown that a more natural light regime seems to be more suitable. Lundova et al exposed specimen to 48 h of natural photoperiod alternating with 24 h of constant light, which resulted in increased somatic growth in both sexes (Lundova et al 2021). Another positive effect was the delayed gonadal development and the onset of puberty (Lundova et al 2021).…”
Section: Light Regime-what Should Be Consideredmentioning
confidence: 99%
“…Lundova et al exposed specimen to 48 h of natural photoperiod alternating with 24 h of constant light, which resulted in increased somatic growth in both sexes (Lundova et al 2021). Another positive effect was the delayed gonadal development and the onset of puberty (Lundova et al 2021). Additionally, Valenzuela et al concluded in their study that a 24/0 regime contributes to increased stress production in rainbow trout (Valenzuela et al 2022).…”
Section: Light Regime-what Should Be Consideredmentioning
confidence: 99%
“…The photoperiod serves as a key cue for animals to modulate their life activities. Fish growth and gonadal development are influenced by the photoperiod, with long-day manipulation applied for healthy growth and early gonadal maturation in ornamental fish [6,7]. Crustaceans, such as crayfish, are susceptible to light signals that affect molting frequency, growth, and reproductive efficiency [8,9].…”
Section: Introductionmentioning
confidence: 99%